2005
DOI: 10.2214/ajr.04.1387
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Interobserver Agreement for Defecography in Fecal Incontinence

Abstract: Reproducibility for enterocele, anterior rectocele, and severity grading is good, but for intussusception is fair to moderate. For anismus, the diagnosis of incomplete evacuation after 30 sec is more reproducible than puborectalis impression. The level of experience seems to play a role in diagnosing anterior rectocele and its grading and in diagnosing intussusception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
0
15
0
3
Order By: Relevance
“…Dynamic magnetic resonance (MR) imaging is used to assess pelvic organ prolapse (2)(3)(4)(5); however, correlation of MR findings with physical examination and cystocolpoproctography results is variable (5)(6)(7). Defecography also has high interobserver variability (8). Measurement reproducibility is important to assess, whether in the research or the clinical setting, since it may affect management of patients with pelvic floor disorders.…”
mentioning
confidence: 99%
“…Dynamic magnetic resonance (MR) imaging is used to assess pelvic organ prolapse (2)(3)(4)(5); however, correlation of MR findings with physical examination and cystocolpoproctography results is variable (5)(6)(7). Defecography also has high interobserver variability (8). Measurement reproducibility is important to assess, whether in the research or the clinical setting, since it may affect management of patients with pelvic floor disorders.…”
mentioning
confidence: 99%
“…Secondly, in spite of a standard protocol for defecography, inaccurate assessment of the rectocele by the radiologist must be considered. The interobserver agreement for posterior wall prolapse represented by point Bp of POP-Q [13]. A third explanation is that relaxation of the vaginal wall does not necessarily go together with bulging of anterior rectal wall, implying that posterior wall prolapse and rectocele are different anatomic disorders and not synonyms for the same condition [14].…”
Section: Discussionmentioning
confidence: 99%
“…anismus) cause [31]. A recent study reported that the reproducibility of diagnosing enterocele, anterior rectocele and their grading in patients with faecal incontinence is good [32]. Diagnosing intussusception and its severity seemed to be more difficult.…”
Section: Imaging Techniquesmentioning
confidence: 99%